Reflections on bird and mammal risk assessment for plant protection products in the European Union: Past, present, and future. (March 2017) - Brooks, Amy C.; Fryer, Mike; Lawrence, Alan; Pascual, Juan; Sharp, Rachel
Abstract: The use of plant protection products on agricultural crops can result in exposure of birds and mammals to toxic chemicals. In the European Union, the risks from such exposures are assessed under the current (2009) guidance document from the European Food Safety Authority (EFSA), designed to increase the realism of the theoretical risk assessments in comparison to its predecessor (SANCO/4145/2000). Since its adoption over 7 yr ago, many plant protection products have been evaluated successfully using the 2009 EFSA guidance document. However, there are still significant areas of improvement recommended for future revisions of this guidance. The present Focus article discusses experiences to date with the current scheme, including levels of conservatism in input parameters and interpretation by regulatory authorities together with proposals for how the guidance document could be improved when it is revised in the not too distant future. Several areas for which further guidance is recommended have been identified, such as the derivation of ecologically relevant bird and mammal reproductive endpoints and the use of modeling approaches to contextualize risk assessments. Areas where existing databases could be improved were also highlighted, including the collation of relevant focal species across Europe and expansion of the residue database for food items. To produce a realistic and useable guidance document in the future, it is strongly recommended that there is open and constructive communication between industry, regulatory authorities, and the EFSA. Such collaboration would also encourage harmonization between member states, thus reducing workloads for both industry and regulatory authorities. Environ Toxicol Chem 2017;36:565–575. © 2017 SETAC